Paternally and maternally imprinted gene perturbed expression in parthenogenetic diploid embryos in Capra hircus - RANJAN, R; SINGH, R; KUMAR, K; SARKAR, M; DAS, B C; BAG, S (The Indian Journal of Animal Sciences, 2018)
The present research work was undertaken to compare the expression of paternally imprinted (P57KIP2, Grb10 and Xist) and maternally imprinted gene (Dlk1) among diploid parthenogenetic (DIP), female sexed in vivo and female sexed in vitro produced embryonic cell colony. The good quality caprine oocytes were matured in presence of cytochalasin B (CCB) and activated by ethanol (7%) for 5 min followed by incubation with 2 mM 6-dimethyl amino purine (DMAP) for 4 h for DIP embryos production. In vivo embryo was collected by surgical method from 10 super ovulated goats using Pluset®. In vitro embryos were produced by maturation of good quality oocyte followed by fertilization with superior male germplasm from the institute flock. Embryonic cell colony were developed from 8 to 16 and morula stage DIP, IVF and in vivo derived embryos. These colonies were used for studying the paternal and maternal imprinted genes expression. Karyotyping and sexing of embryonic cell colony was done to get only female sexed colony for this purpose. Paternally imprinted genes (P57KIP2, Grb10 and Xist) showed more expression in DIP compared to in vivo and IVF derived embryonic cell colony. The expression of maternally imprinted genes (Dlk1) was low in DIP compared to in vivo and IVF derived embryonic cell colony. The present study demonstrated that the expression profile of both paternal and maternally imprinted genes were perturbed, which may be responsible for developmental failure of parthenogenetic embryos to full term following parthenogenetic embryo transfer in goat.